Nilai-nilai Pendidikan Islam dalam Konten Tema Sedekah pada Chanel YouTube Pratiwi Noviyanthi - Khairunisa, Khairunisa; Kanus, Oktari (Lembaga Yasin AlSys, 2025)
This study is motivated by the phenomenon of the increasing popularity of charity content on social media, particularly on the YouTube channel of Pratiwi Noviyanthi, which not only plays a role in providing aid but also spreads values of kindness and inspires many. However, behind the public appreciation, this content also faces diverse responses regarding the authenticity of its intentions and its long-term impact. The aim of this research is to explain the Islamic educational values embedded in the charity-themed content on Pratiwi Noviyanthi’s YouTube channel, the way they are presented, and the impact they have on the audience and the recipients of the aid. This research uses a qualitative approach with a case study type of research, employing literature study, observation, and content analysis methods for data collection. The results indicate that the Islamic educational values in the content encompass aspects of aqidah (such as faith, tawakal, and gratitude), shari'ah (such as helping others, sharing, and charity), and akhlak (such as empathy, compassion, and sincerity). These values are conveyed naturally through exemplary actions, Islamic language, inspirational stories, and direct invitations to the audience. The impact is felt positively, both by the audience, who are inspired to increase their social concern and faith, and by the aid recipients, who experience physical, mental, and spiritual changes. The main conclusion of this research is that Pratiwi Noviyanthi's charity content is not only entertaining but also effectively internalizes Islamic educational values in the digital society. The implications of this research include theoretical benefits, such as the development of Islamic education concepts in social media and as a reference for future research, as well as practical benefits, such as serving as a guideline for content creators, society, and policymakers in creating educational and ethical digital content.